PERANCANGAN STRUKTUR BETON BERTULANG GEDUNG HOTEL AL-HAJJ 6 LANTAI JALAN LETNAN JENDRAL SUTOYO KOTA PONTIANAK: PERANCANGAN STRUKTUR BETON BERTULANG GEDUNG HOTEL AL-HAJJ 6 LANTAI JALAN LETNAN JENDRAL SUTOYO KOTA PONTIANAK - idiris, nurianda; Asmadi, Asmadi; Syahrani, Deny; setiawan, randy (Jurusan Teknik Sipil Polnep, 2021)
Hotel Al-Hajj 6 (six) floors is a supporter of infrastructure for Hajj pilgrims and is also common with thelocation of the hotel in the middle of the city, namely in the district of South Pontianak, Pontianak City Designof reinforced concrete structure Al-Hajj hotel building is planned 6 floors with 3 star hotel standards.Indesigning this hotel prioritizes the strength of structure with the concept of reinforced concrete.This hotel-life method collects soil data and image data as a basis for calculations. In its depiction using theAutoCad program and engineering analysis using the SAP 2000 3D program and the calculation of buildingstructures refers to SNI 03-2847-2013 for concrete structures, SNI 1727-2013 regarding minimum load andLoading Planning for Houses and Buildings (PPURG) 1987 and SNI 1729-2019 for earthquake-resistantbuilding structures.The result of the design of the structure in the form of thick 90 mm shop floor plate with reinforcement φ6 andground floor s / d 6th floor has a plate thickness of 130 mm φ8, the dimensions of the parent beam structure are40 x 70 cm with tree bone D19 and bone begel φ8-320 mm child beam 30 x 60 cm bone tree D16 and bone φ8-270 mm and ring beam and bone begel φ6-170 mm and for ring beam 20 x 40 cm bone tree D16. Columndimensions 60 x 60 cm of tree bone D22 and bone begel φ8-190 mm foundation using a stake of 450 x 450 mmwith pile cap 3.9 x 3.9 with bone and solid bone with a depth of 22 m. From the results of the design andcalculation of the structure of this hotel can be applied on the ground and for analytical purposes in theplanning of the next building.